Study on the Optical Properties of Water in Yinjia Lake in Summer - WU Chao; WU Xiaodong; GE Xuguang; WANG Wei; FENG Lian; YANG Jiuyun; TAN Ya (Renmin Zhujiang)
To explore the optical properties and impact factors of water in summer,and to provide reference with the submerged macrophytes restoration in Daye urban lakes,the study on Yinjia Lake,a typical urban lake in Daye City,Hubei Province in the summer of 2017 was conducted by field investigation and indoor analysis.The results show that:①The average secchi depth(SD) in Yinjia Lake in summer is (0.29±0.09) m,the average optical attenuation coefficient (Kd) is (3.52±0.16)/m;②The average concentration of suspended solids (SS) is (38.60±14.66) mg/L,the average concentration of chlorophyll-a (Chl-a) is (14.80±7.80) μg/L,and that of chromophoric dissolved organic matter (CDOM) is (11.49±1.55) μg/L.It can be concluded that:①The Pearson correlation coefficients of Kd with Chl-a,CDOM and SS are 0.572,0.078 and 0.835 respectively,the main impact factor of Kd is SS,followed by Chl-a and CDOM;②According to the euphotic depth (Zeu)/water depth (depth) threshold,the submerged macrohytes in most waters of Yinjia Lake could not recover naturally in summer,and some auxiliary engineering measures such as controlling water level and reducing suspended solids are employed to improve the underwater lighting conditions.